"Just for a Couple of Cinemas and Very Cheap". Feature Films in the Business Plans of Prague Producers between 1911 and 1915 - Večeřa, Michal (Iluminace, 2017)
Before 1915, film production in Czech lands was in its beginnings and further development was limited by many factors - from the lack of money to problems with distribution. Contemporary entrepreneurs had to find their way to minimize the risk of financial loss - their efforts usually lead to the diversification of activities. Presented study aimes to analyze the problem on the example of the first four Czech producers - Kinofa, Illusionfilm, Lucernafilm and ASUM. Depending on applied strategies, these companies can be further divided in two groups. While ASUM tried to make multiple-reel fiction movies using the star image of Andula Sedláčková, the other three concentrated itself mainly in the area of nonfiction films and adverts. Presented text is organized in three subchapters - I move from the analysis of fiction film production to the analysis of overall production activities of the companies. The third and final part focuses on distribution, which was crucial for the success of producers. Czech production made during the period can be seen as an example of cinema of small nation that struggled due to its provinciality, small market and late start in comparison with stronger rivals from abroad.
Keywords: distribution companies; film production; production activity; film distribution; the beginnings of film